The effect of zinc oxide and aluminum oxide nanoparticles on interfacial tension and viscosity of nanofluids for enhanced oil recovery - Zaid, H.M. (Trans Tech Publications Ltd, 2014)
Application of nanotechnology in enhanced oil recovery (EOR) has been increasing in the recent years. After secondary flooding, more than 60 of the original oil in place (OOIP) remains in the reservoir due to trapping of oil in the reservoir rock pores. One of the promising EOR methods is surfactant flooding, where substantial reduction in interfacial tension between oil and water could sufficiently displace oil from reservoir. The emulsion that is created between the two interfaces has a higher viscosity than its original components, providing more force to push the trapped oil. In this paper, the recovery mechanism of the enhanced oil recovery was determined by measuring oilnanofluid interfacial tension and the viscosity of the nanofluid. Series of core flooding experiments were conducted using packed silica beads which replicate core rocks to evaluate the oil recovery efficiency of the nanofluid in comparison to that using an aqueous commercial surfactant, 0.3wt sodium dodecyl sulfate (SDS). 117 increase in the recovery of the residual oil in place (ROIP) was observed by the 2 pore volume (PV) injection of aluminium oxide nanofluid in comparison with 0.3wt SDS. In comparison to the type of material, 5.12 more oil has been recovered by aluminium oxide compared to zinc oxide nanofluid in the presence of EM wave. The effect of the EM wave on the recovery was also studied by and it was proven that electric field component of the EM waves has been stimulating the nanofluid to be more viscous by the increment of 54.2 in the oil recovery when aluminium oxide nanofluid was subjected to 50MHz EM waves irradiation. Â© (2014) Trans Tech Publications, Switzerland.